Mastering risks of damage and risks of crisis: the role of organisational learning. (21st September 2004) - Wybo, Jean-Luc
Mastering risks, accidents and crisis is a complex task which is achieved by a large number of stakeholders. In order to determine appropriate responses to risk-prone situations, researchers propose a classification in two categories: risks of damage and risks of crisis. Risks of damage correspond to situations that have been studied and for which preventive and protective measures have been taken by the organisation. In other words, there is a plan in place in the organisation. Risks of crisis, on the other hand, correspond to situations where there has been little anticipation and no previous experience and as a consequence, no preventive and protective measures have been taken by the organisation. There is no plan in place or the plan is inadequate or inoperable. Either of these situations may put the organisation into chaos, although chaos and confusion are more likely with risks of crisis. Special attention is given in this paper to the origins of crisis situations and emergence of ad-hoc organisational patterns among their management. A case study is presented to illustrate how an ad-hoc organisation has emerged during the management of the crisis that followed the Erika oil spill on the French coasts in December 1999. This paper presents the advantages associated with the development of organisational learning to analyse accidents and crisis: a better sharing of knowledge about identification of weaknesses and strengths, and a deeper involvement of people in risk mastering.